Pediatric Robotic Surgery in South America: Advantages and Difficulties in Program Implementation - Moldes, Juan M.; de Badiola, Francisco Ignacio; Vagni, Roberto Luis; Mercado, Pedro; Tuchbaum, Virginia; Machado, Marcos G.; López, Pedro José (Frontiers in Pediatrics, 2019)
Robotic assisted laparoscopic surgery is gaining popularity around the world due to its vast benefits. Although it has been established mainly in developed countries, in South America the robotic programs have become more popular, but its growth is clearly slower. Information about robotic pediatric surgery program in Brazil, Chile, Uruguay and Argentina was collected through e-mail surveys. Results were analyzed and compared to worldwide information about robotic surgery. Due to the wide social, economical, and technological gap between hospitals in South America, it is hard to develop a proper pediatric robotic surgery program. The main obstacles in those four countries appear to be a combination of high purchase costs and equipment maintenance, lack of financial coverage of the procedure by insurance companies and the absence of significant benefits proved in pediatrics in relation to laparoscopic surgery. The pediatric specialties are in the process of making and implementing robotic programs supported by the evident development in adult specialties. However, pediatric robotic surgery in Brazil, Chile, Uruguay and Argentina do not seems to share that growth.